(untitled) (Nordic Journal of African Studies, 2002)
In this article the potential of the multilingual Web to function as a corpus, in addition to a source for corpus creation, is examined. Despite the fact that English dominates the Web, and despite the fact that most work in corpus linguistics revolves around English, it will be argued that African languages do have a place in the bigger picture. Substantial African-language Web corpora can indeed already be compiled (Web for Corpus) and accessed (Web as Corpus), and the list of potential applications grows by the day.